A review on benefits, potential and conservation of Baccaurea lanceolata - Monjia Mojulat; Noumie Surugau (IOP Publishing Ltd., 2021)
Malaysia has introduced the Plant Genetic Resources for food and agriculture (PGR) policy to further research and profile its wild crops to conserve and protect its rich biological diversity. There is an urge for relevant research to be conducted since it may also serve as an identifying accession of desirable traits for crop improvement. One such underutilised plant, Baccaurea lanceolata or locally known as “liposu” by the Dusun people has long played a traditional and cultural role for the local Bornean people. Unfortunately, although in recent years it has gained traction as a traditional food delicacy among the locals, it has remained underutilised and not commercially cultivated due to limited research and exposure. Despite that, limited studies on plants of Baccaurea species have been shown to contain various beneficial properties. The underutilised fruit of Baccaurea lanceolata has a high probability of containing a health beneficial, noteworthy amount of unique, uncovered phytochemicals. Research on this underutilised plant may also provide a path to road of commercialisation as well as preserving this tree from the danger of forest clearing. This review paper has therefore compiled information from available secondary literature on Baccaurea lanceolata in terms of its traditional knowledge, cultural usage as well as studies on its scientifically proven health benefits.